2020
DOI: 10.1111/mam.12222
|View full text |Cite
|
Sign up to set email alerts
|

A review of ecological factors promoting road use by mammals

Abstract: Roads have numerous negative impacts for mammals, but may also serve as attractants due to altered vegetation or provisioning of resources. We reviewed the use of roads and their associated features by mammals, in order to understand the ecological factors contributing to road use. We documented 129 studies that recorded road use by 116 mammalian species, spanning 15 orders and 35 families, in six continents. Carnivora was the most common order (40 species, 34% of all 116 species), followed by Artiodactyla (24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 117 publications
0
40
1
1
Order By: Relevance
“…Due to altered vegetation or resource provisioning, roads can serve as attractants to animals. For this reason, a recent review concluded that road use contributes to the risk of collisions with vehicles (Hill et al 2020). Furthermore, animal migration may also lead to the dispersal of infectious agents, which can have unpredictable effects and cause difficult-to-control diseases (Kirkwood and Sainsbury 1996).…”
Section: Flight From the Firementioning
confidence: 99%
“…Due to altered vegetation or resource provisioning, roads can serve as attractants to animals. For this reason, a recent review concluded that road use contributes to the risk of collisions with vehicles (Hill et al 2020). Furthermore, animal migration may also lead to the dispersal of infectious agents, which can have unpredictable effects and cause difficult-to-control diseases (Kirkwood and Sainsbury 1996).…”
Section: Flight From the Firementioning
confidence: 99%
“…Understanding why WVCs occur requires knowledge of animal behavioral responses to roads and to vehicles (Figure II). Road avoidance can be caused by traffic noise, road surface, or the presence of vehicles [43,44], and is linked to the more indirect impacts (e.g., as barriers or filters to movement). Conversely, road attraction increases wildlife-vehicle interactions by prompting a crossing attempt or increasing road use due to thermoregulation, habitat or food resource availability, and dispersal or breeding behavior.…”
Section: Box 2 Wildlife-vehicle Collisions As a Threat To Biodiversitymentioning
confidence: 99%
“…Animal mortality in collisions with vehicles on roads is an effect of an increase in road infrastructure of global importance (e.g., Hels and Buchwald 2001;Forman et al 2003;Ruiz-Capillas et al 2015;Hill et al 2019;Schwartz et al 2020;Grilo et al 2021). Mortality rates on roads may be attributed to various factors related to the greater activity of animals in road corridors, such as crossing the roads from home ranges located in the neighborhood of roads or using a road as a feeding ground (Trombulak and Frissell 2000;Jaarsma et al 2006;Sabino-Marques and Mira 2011;Hill et al 2021).…”
Section: Introductionmentioning
confidence: 99%